Gender Differences in Clinicoepidemiological Features of Vitiligo: A Cross-Sectional Analysis. (13th February 2014) - Patil, Sharmila; Gautam, Manjyot; Nadkarni, Nitin; Saboo, Neha; Godse, Kiran; Setia, Maninder Singh
Abstract : Background . Vitiligo has important clinical and social consequences particularly in the pigmented skin. The present study was conducted to assess the differences in clinicoepidemiological presentation of vitiligo in males and females and to understand the factors associated with spread of vitiligo in them. Methods . This is a cross-sectional analysis of secondary clinical data of 168 vitiligo patients at a tertiary medical centre at Navi Mumbai. We used logistic regression models to estimate the association between gender and clinical characteristics of vitiligo and to evaluate the factors associated with spread of vitiligo. Results . There were no significant differences between the mean ages of males and females; however, males reported a longer duration of disease (6.9 (10.4) years) compared with females (4.9 (7.4) years). Males were significantly more likely to report a family history of vitiligo compared with females (adjusted OR (aOR): 16.87, 95% CI: 2.16 to 131.69). Even though females were more likely to report spread of lesions, the association was not statistically significant (OR: 1.21, 95% CI: 0.62 to 2.36). Discussion . The differences in the clinical presentations between genders highlight the need to understand the different factors (possibly genetic) that may play a part in the pathogenesis of this multifactorial disease in males and females.